Material and solar cell research in high efficiency micromorph tandem solar cell - Hafezi, Razagh; Karimi, Soroush; Jamalzae, Sharie; Jabbari, Masoud (Ciência e Natura, 2015)
“Micromorph” tandem solar cells consisting of a microcrystalline silicon bottom cell and an amorphous silicon top cell are considered as one of the most promising new thin-film silicon solar-cell concepts. Their promise lies in the hope of simultaneously achieving high conversion efficiencies at relatively low manufacturing costs. The concept was introduced by IMT Neuchâtel, based on the VHF-GD (very high frequency glow discharge) deposition method. The key element of the micromorph cell is the hydrogenated microcrystalline silicon bottom cell that opens new perspectives for low-temperature thin-film crystalline silicon technology. This paper describes the use, within p–i–n- and n–i–p-type solar cells, of hydrogenated amorphous silicon (a-Si:H) and hydrogenated microcrystalline silicon (_c-Si:H) thin films (layers), both deposited at low temperatures (200_C) by plasma-assisted chemical vapour deposition (PECVD), from a mixture of silane and hydrogen. Optical and electrical properties of the i-layers are described. Finally, present performances and future perspectives for a high efficiency ‘micromorph’ (mc-Si:Hya-Si:H) tandem solar cells are discussed.